Fear of Recurrence of Atrial Fibrillation: Translating a Cancer Fear Model to the Atrial Fibrillation Patient Experience - Anthony, Scarlett; Harrell, Rebecca; Martin, Caroline; Hawkins, Taylor; Khan, Saleen; Naniwadekar, Aditi; Sears, Samuel F. (Frontiers in Psychiatry, 2022)
Background: Atrial fibrillation occurs when rapid and disorganized electrical signals cause the atria in the heart to beat irregularly and is associated with an increased risk for stroke. Despite medical advancements, first and second line atrial fibrillation treatments exhibit significant recurrence rates. Because of this, atrial fibrillation patients often experience disease-specific fears that are not routinely assessed and targeted in clinical management. Fear of recurrence models in cancer research and other cardiac-specific fears have paved the way for a patient-centric approach to disease intervention. Purpose: Clinical assessment focused solely on the taxonomy of anxiety disorders may miss key components unique to the atrial fibrillation patient experience. An anxiety disorder diagnosis in the presence of an arrhythmia could be misleading and ultimately fail to address patient needs. Modeled from the cancer literature, providers may benefit from a broader disease specific conceptualization for AF patients that differs from a general DSM-5 diagnosis. Aims: The objectives of this paper are: 1) to review the medical aspects of atrial fibrillation, 2) to examine the comparability of fear of recurrence concept from cancer literature to the atrial fibrillation patient, and 3) to suggest considerations of these novel concepts in patient care. Future Directions: Increased understanding of fear of recurrence among atrial fibrillation patients aims to define and assess fear of recurrence components, determine treatment targets, and ultimately improve patient outcomes.